المختصرات الفقهية عند فقهاء إباضية المغرب كتاب النيل انموذجا (El-Wahat Journal for Research and Studies, 2021)
The Jurisprudential Authorship Of The Ibadi Of The Maghreb- Especially The Later Ones - Is Characterized By A Desire To Limit Themselves To Important Issues That Are Easy For Students To Memorize And Invoke. One Of The Most Prominent Of These Acronyms Is The Book Of Ennile Wa Chifaa El Alil To Abdul Aziz Al-Thamini, In Which He Gathered All What Was Produced By The Early Ibadhi Scholars, In A Manner That Accurately Distinguishes It From The Latest Scholars . Similar To Sheikh Mhamed Tfayyesh, Who Explained It In His Famous Encyclopedia The Book Of Ennil Wa Chifaa El Alil. Key Words - Acronyms; Jurisprudence; Ibadi Of The Maghreb; The Book Of Ennile.